2019
DOI: 10.1016/j.jjcc.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of synthesized right-sided chest electrocardiograms in patients with acute pulmonary embolism

Abstract: Background: The significance of right-sided chest lead electrocardiogram (ECG) abnormalities in acute pulmonary embolism (APE) is unclear. This study evaluated the characteristics of such abnormalities in APE patients. Methods: This retrospective study included consecutive patients who were diagnosed with APE by contrast-enhanced computed tomography or pulmonary artery angiography. A standard 12-lead ECG and a synthesized right-sided chest ECG were obtained from these patients. Waveform differences were noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…It has been postulated that biochemical abnormalities and hypoxia of the myocardium and His-Purkinje system cause slowing conduction in the right ventricle. Studies have shown that ST-segment and T-wave changes are associated with acute pulmonary embolism [ 3 , 5 ]. Our patient’s T-wave inversion in V1 to V5 and lead II, III, and AVF concur with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that biochemical abnormalities and hypoxia of the myocardium and His-Purkinje system cause slowing conduction in the right ventricle. Studies have shown that ST-segment and T-wave changes are associated with acute pulmonary embolism [ 3 , 5 ]. Our patient’s T-wave inversion in V1 to V5 and lead II, III, and AVF concur with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple literature reviews have described changes in ECG in acute pulmonary embolism; however, it has low specificity. ECG changes, such as sinus tachycardia, S1Q3T3, and right strain pattern, have been described, and they show a correlation with acute pulmonary embolism despite low sensitivity [1][2][3][4][5]. Biphasic T wave inversion in the precordial lead has been described as Wellens' pattern ECG and correlates with coronary artery occlusion rather than acute pulmonary embolism [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, Kusayama et al also indicated that T inversion in V3R lead is highly diagnostic for APE. 14 Beyond the diagnostic properties of ECG in patients with APE, evidence suggests that ECG abnormalities were independently associated with prognosis and survival rate of patients with APE. Sinus tachycardia in companion with signs of right ventricular dysfunction is associated with poor prognosis in patients with APE.…”
mentioning
confidence: 99%
“…13 Recently, Kusayama et al also indicated that T inversion in V3R lead is highly diagnostic for APE. 14…”
mentioning
confidence: 99%